Creation of objective performance criteria among medical devices. Issue 1 (1st August 2022) - Gressler, Laura Elisabeth; Marinac-Dabic, Danica; dosReis, Susan; Goodney, Philip; Mullins, C. Daniel; Shaya, Fadia
Abstract : Objectives: Objective performance criteria (OPC) may serve as a tool to expedite the approval process and continue active surveillance of class III medical devices. Thus far, published guidance on the creation of OPC has been clinical area-specific. This study aimed to capture reflections from key stakeholders on the creation of OPC that may serve as a precursor for a formalized conceptual framework within the USA. Design: Reflections from key stakeholders and guidance from an advisory committee were captured to gain an understanding of the elements that are crucial to the generation of OPC. Setting: A non-probability sampling method using the purposive sampling strategy was employed to identify relevant stakeholders for engagement in semi-structured, open-ended, concept elicitation discussions. Participants: Stakeholders involved in the generation of OPC. Main outcome measures: Elements and themes regarding the priorities of, experiences with, roles within and perceived challenges associated with OPC creation captured through a phenomenological approach. Results: A total of 27 participants were engaged to represent the following contributors: representatives of registries, health systems, health technology assessment bodies, clinicians, device application reviewers, payers, patients, patient representatives, patient caregivers, device manufacturers, data coordinators, data analysts and data informaticians. Consensus was achieved on the five core elements: (1) identification of medical devices, (2) engagement of key stakeholders, (3) selection of data source, (4) performance of appropriate statistical analyses and (5) reporting of findings. The engagement of key stakeholders (38%) was cited most frequently as the most important core element. Access to meaningful and high-quality data sources (47%) was the most frequently mentioned challenge. Conclusions: The reflections from the participants identified five elements to be considered when generating an OPC within class III medical devices and may provide the needed foundation for the development of official guidance on OPC generation.